2011
DOI: 10.2134/agronj2010.0187
|View full text |Cite
|
Sign up to set email alerts
|

Forage Radish Cover Crop Suppresses Winter Annual Weeds in Fall and Before Corn Planting

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. F orage radish is a new winter annual cover crop in the Mid-Atlantic region. Early work with forage radish as a cover crop in this region included observations that it could provide dramatic fall and spring weed suppression (Weil and Kremen, 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
63
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 11 publications
9
63
3
5
Order By: Relevance
“…niger, V. sativa, M1 and M2 achieved a significant decrease of weed population compared to the untreated control. Similar results were observed during autumn period in the study of Lawley et al (2011). Five WAS differences of the weed suppressive ability can be observed between treatments.…”
Section: -2supporting
confidence: 87%
“…niger, V. sativa, M1 and M2 achieved a significant decrease of weed population compared to the untreated control. Similar results were observed during autumn period in the study of Lawley et al (2011). Five WAS differences of the weed suppressive ability can be observed between treatments.…”
Section: -2supporting
confidence: 87%
“…Corn grain moisture (188 g kg -1 ) and test weight (42.3 g cm -3 ) were greatest following early-planted radish; however, no significant difference in grain yields occurred in moderate-(2013) and high-yield (2014) environments at preplant N rates typical for this region. This was similar to other research evaluating corn's rotational response to cover crops with radish (Lawley et al, 2011). However, there is some research that has shown a yield increase in subsequent crops such as sweet corn following radish (Malik et al, 2008) which was related to increased weed suppression.…”
Section: Winter Annual Weed and Corn Response The Following Yearsupporting
confidence: 85%
“…However, in 2014 no differences among planting dates were observed. Research has shown that Brassica species includeing radish have significant weed suppression (Altieri et al, 2011;Lawley et al, 2011Lawley et al, , 2012Malik et al, 2008;Norsworth, 2003;Stivers-Young, 1998;Uremis et al, 2009). Norsworthy (2003) showed that germination and radical growth of all weed species [sickle pod (Senna obtusifolia L.), prickly sida (Sida spinosa L.), and yellow nutsedge (Cyperus esculentus L.)] evaluated were reduced by extract of forage radish in comparison to non-treated controls.…”
Section: Winter Annual Weed and Corn Response The Following Yearmentioning
confidence: 99%
See 2 more Smart Citations